Polanyi vs Hayek? - Mirowski, Philip (Globalizations, 2018)
Karl Polanyi and Friedrich Hayek are often portrayed as implacable intellectual opponents but their respective historical trajectories suggest some telling similarities. Here we describe some key similarities in their approach to markets, as a prelude to evaluating the political consequences of relying upon their Austrian conceptions of nature-based and constructivist framing of markets. Perhaps it is time to transcend their dichotomy.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; POLANYI, Karl, 1886-1964; POLANYI, Michael, 1891-1976; constructivism; markets; science and technology; spontaneous order

Re-dynamising Local Economies in the Age of Trumpism - Bauwens, Michel; Niaros, Vasilis (Journal of Futures Studies, 2017)
The article presents the authors' arguments on the political and policy response behind the rise of Trumpism according from the analysis of authors Kojin Karatani, Karl Polanyi and Mark Blyth. Topics discussed include Karatani's book "The Structure of World History" on the integration of modalities for political and economic system, Polanyi's analysis in the book "The Great Transformation" on the systemic balance and the transition in regimes of value for re-alignment of modalities.
Keywords: BLYTH, Mark; Futures studies; Great Transformation, The (Book); KARATANI, Kojin; Structure of World History: From Modes of Production to Modes of Exchange, The (Book); TRUMP, Donald; Trumpism; disembeddedness; local economies; technology

Economics Humanized - Pearson, Dan (Issues in Science & Technology, 2015)
Keywords: BLOCK, Fred L.; Power of Market Fundamentalism: Karl Polanyi's Critique, The (Book); SOMERS, Margaret R.; book review; economics; nonfiction; science and technology

Nano-worlds as Schumpeterian emergence and Polanyian double-movements - Randles, Sally; Dewick, Paul; Loveridge, Denis; Schmidt, Jan C. (Technology Analysis & Strategic Management, 2008)
The overarching question raised in this special issue is whether societies can, do or indeed should steer new and emergent science and technological development and its management on to trajectories construed as more or less 'desirable'. It therefore sits at the interface of two arenas. These are governance: processes of shaping/steering emergent technologies and markets; and sustainability: normative agendas incorporating a range of potentially competing conjectures and internally inconsistent desires such as to facilitate rather than stifle innovation, to enable economic development, to anticipate or deploy strategies to cope with risk and uncertainty, and to encourage technological developments that benefit rather than harm humans, their quality of life and the natural environment. Despite the potential for apparent empirical inconsistencies and contradictions that manifest as outcomes of the negotiation of these aims, there is (pace Karl Polanyi) a normative entry point to all of the articles and the material they draw upon, which is the idea that markets and technologies should be the handmaiden of societies, not vice versa. It is now widely recognized that 'nanotechnology' is a diverse set of feasible procedures emerging from scientific possibilities to enable the production of artefacts at the nanoscale creating new products, processes and services. Attention has to be paid to the desirability of these artefacts, which involve social, economic, ecologic, political and ethical matters that surround their emergence. The purpose of this special issue is to set out the current and future prospects for the widespread use (or innovation) of technological convergence at the nanoscale to create nano-artefacts, and the needs for governance and regulation that will accompany these innovations.
Keywords: POLANYI, Karl, 1886-1964; SCHUMPETER, Joseph Alois, 1883-1950; double movement; economic development; editorials; emergence; governance; nano-; nanotechnology; new product development; quality of life; sustainability; technological innovations